Eficiência nas emissões de gás carbônico nos países desenvolvidos e em desenvolvimento - Pellenz, Jéssica de Lima da Vida (2019)
In the current context, where a number of catastrophic phenomena arising from climate change are placing many concerns and challenges on humanity, it is natural that climate policy-makers should be aware of how countries are, not only using natural resources in their production processes, but also how each nation contributes to the accumulation of greenhouse gases (GHG) in the atmosphere. Therefore, the need of plotting strategies to mitigate the harmful effects of global warming has led to joint articulations actions among countries around the world. However, for these strategies to lead to the solution of the problems, a deep knowledge of the characteristics of each country is necessary as far as its current and historical environmental performances are concerned. Considering also that climate changes can jeopardize the continuous economic growth, it is necessary to understand how the environmental variables are related to the economic ones. In this sense, the present study intends to investigate the relationship between CO2 emissions, a major GHG originated from human action, and economic growth, as well as to verify the environmental performance of these emissions in a sample of 161 countries included in the Paris Agreement. By means of the Stochastic Production Frontier estimation, the technical and environmental efficiency scores have been calculated through a data panel comprising 161 groups and 28 years, resulting in 4508 observations. To the traditional inputs of the neoclassical production function (capital and labor), the variables "CO2 emissions" were incorporated, aiming to analyze the importance of that for the increase in the countries’ GDP, and a variable of time, with the purpose of obtaining the effects of technical progress. Comparisons were made between sample countries with emphasis on the differences between developed and developing countries. The main results suggest that CO2 emissions are indeed essential to economic growth, especially in industrialized countries. Technical progress has led to an improvement in the performance of all inputs (including emissions) in developed countries. However, in developing countries, it appears to have led to a reduction in the use of the "labor" factor, and does not help to make better use of emissions as input. The analysis of the efficiencies suggests that the technical performance of the countries was much higher than the environmental performance, showing a medium score of technical efficiency relatively high, while the average environmental scores were very low. The industrialized countries were the ones that presented the greatest scores of technical efficiency, but they were inefficient on CO2 emissions.